Reinterpretation of Disaster Verses in Preventing Covid-19 : (Analysis Maqashidi’s Interpretation Perspective) - Safira Malia Hayati (Jurnal Ushuluddin, 2021)
This article answers how the reinterpretation of disaster verses for the prevention of Covid-19 and how to apply maqashidi interpretation and maqashid values conveyed by the Qur'an in verses and hadiths related to the prevention of Covid-19. The method that the author uses is the interpretation method, this method aims to explore the messages of the Qur'an in revealing verses about the disaster prevention against Covid-19. This study also uses the thematic method, namely discussing verses based on a set theme, aiming to gain an understanding of the interpretation of disaster verses regarding the contextuality of Covid-19 prevention. Thus, the author comes to the conclusion; first, everything that happens is the will of Allah SWT in accordance with the level of ability of His servants. So as a servant should not give up in the face of it. Second, as a form of endeavor to prevent this epidemic by complying with policies and obeying the orders of Ulil Amri (Government) and the fatwas of Ulama in terms of the protocol for preventing the transmission of Covid-19, this is proof of our faith in the provisions and laws of Allah as a people. obedient. Then, there are at least five maqashid values conveyed by the Qur'an in reinterpretation using the maqashidi interpretation perspective, namely; hifdz ad-Din, al-Nafs, al-'Aql, al-Nasb, and al-mâl. This article is expected to contribute to the Indonesian Muslim community in dealing with and preventing the spread of the Covid-19